2007
DOI: 10.1007/s12130-007-9033-5
|View full text |Cite
|
Sign up to set email alerts
|

Metaphors for the Mobile Internet

Abstract: This paper examines a set of metaphors for describing, understanding and characterising the Mobile Internet. The metaphors are a result of extensive user studies in the US, Hong Kong and Europe in the late 2006 and early 2007.In these studies, we explored the user experience related to the Mobile Internet through in-depth contextual interviews with over 40 users, including a group in the US, which was deprived of their standard Internet PC access for several days. Our analysis of the collected data resulted in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 8 publications
0
21
0
Order By: Relevance
“…This idea is based on previous research that shows that people are confused on how much they spend when using the mobile Internet [9]. Wrong estimations of the Internet fee and the high perception about the Internet fee are considered to have an impact on the adoption of the mobile Internet [10].…”
Section: A Educational Content Delivey Costmentioning
confidence: 99%
See 1 more Smart Citation
“…This idea is based on previous research that shows that people are confused on how much they spend when using the mobile Internet [9]. Wrong estimations of the Internet fee and the high perception about the Internet fee are considered to have an impact on the adoption of the mobile Internet [10].…”
Section: A Educational Content Delivey Costmentioning
confidence: 99%
“…These results reflect a preference towards the low multimedia quality clip, even though the subjects know they have a lower quality. This preference could be explained by the price of mobile Internet that is too high [1,3,5,8,10]. In the last phase, the subjects were given information about the price they need to pay if they exceeded the quantity of data included in the bundle.…”
Section: Mm5 Physicsmentioning
confidence: 99%
“…For example, it has been shown that people are optimising their time spent on the Internet if the billing plan is not unlimited (Roto et al, 2006) and people own past experiences or highly publicised stories that report high billing plans are likely to have an effect on how people use and interact with mobile data (Isomursu et al, 2007). Marcus and Godlovitch (2013) showed that consumers use more intensively mobile data when they are connected to a Wi-Fi network and speculate that the reason may be rationing the consumption on mobile phones.…”
Section: Related Workmentioning
confidence: 99%
“…Isomursu et al refer to the campfire concept as one of six metaphors they identified out of contextual user interviews regarding their use of the mobile Internet [8]. They build on previous work by Thornburg [18] who used the campfire metaphor in learning context and use it to describe the fact that usage of mobile Internet often tends to aim at keeping in touch with one's own social environment, regardless of one's location.…”
Section: Related Work and Conclusionmentioning
confidence: 99%